Europeanisation of the Slovak Legal System - Bárány, Eduard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Europeanisation of a national legal system represents an example of legal pluralism. It occurs in the context of mutual cultural influence between European countries and power relations between European union and member states. There is also the important influence of Council of Europe law. This process has minimally three lines: the Europeanisation of normative texts, judicial decision, and day to day legal life. The constitutional regulation of relations of the Slovak legal order with international law and EU one has developed and nowadays it is open to EU law.
Keywords: europeizacja; Unia Europejska; prawo unijne; Europeanisation; European Union; EU law